Comparing Health Anxiety and Social Exclusion in the Elderlies and Adults Referring to the Veterans Foundation in COVID-19 Pandemic - Kouchaksaraei, Sajjad Ranjbar; Vizeshfar, Fatemeh; Ghaemmaghami, Parvin; Abbasi, Fatemeh (Coronaviruses, 2025)
ObjectiveCOVID-19 pandemic is a global challenge negatively affecting various aspects of health of different age groups. One of the groups involved with the psychological challenges of COVID-19 were the veterans and their families. So, this study was conducted to compare the health anxiety and social exclusion in elderlies and youths referring to the Veteran Foundation in COVID-19 pandemic.MethodsThis descriptive study was conducted on 114 clients of the Veterans Foundation in order to compare the health anxiety and social exclusion in the elderlies and adults referring to Veterans Foundation in the COVID-19 pandemic. The participants were collected through convenience sampling. Data were collected using demographic, health anxiety and social exclusion questionnaires.ResultsIn the comparison of social exclusion and its sub-dimensions, the variables of Out-group social support, participation and shame have a significant difference (p < 0.05) and the average of out-group support in the adults is more than in the elderlies, while the average of participation and social shame is higher in the elderlies than the adults. There is an inverse and significant correlation between the indicators of social relations, participation and the total social exclusion with health anxiety in youths (p < 0.05).ConclusionGiven the risks of social exclusion on the physical and mental health of the elderlies and its correlation with health anxiety, it seems that, more attention should be paid to the effects of the disease on the mental and social health of the elderlies in COVID-19 prevention programs.
Keywords: adults